2018
DOI: 10.1186/s41936-018-0014-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome b shows signs of adaptive protein evolution in Gerbillus species from Egypt

Abstract: Background: Amino acid polymorphisms in the mitochondrial cytochrome b (cytb) gene of four Gerbillus species have been investigated for their geographical distribution and possible functional significance. The sequences were obtained from a total of 20 specimens representing four species of genus Gerbillus collected from Siwa Oasis, Dabaa, Wadi El Natron, El Faiyum, and Baltim in Egypt. Results: Our results identified a group of amino acid variant polymorphisms that were useful for both species taxonomic and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The establishment of population-specific genetic variants may be further propelled by social monogamous behavior and multigenerational natal philopatry leading to genetic differentiation between populations, as already shown for the island populations of Crete and Sardinia [27,28]. Although our selection analysis did not reveal the presence of variants favored by selection, and all mutations were defined as neutral, the same analysis showed that the Cytb gene is under strong purifying selection, which eliminates all substitutions that could have a negative effect on phenotype, as shown in the case of low-altitude deer mice [87] and four different Gerbillus species [55]. The second reason behind genetic differentiation between populations may be specific morphological and reproductive differences in different climates.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The establishment of population-specific genetic variants may be further propelled by social monogamous behavior and multigenerational natal philopatry leading to genetic differentiation between populations, as already shown for the island populations of Crete and Sardinia [27,28]. Although our selection analysis did not reveal the presence of variants favored by selection, and all mutations were defined as neutral, the same analysis showed that the Cytb gene is under strong purifying selection, which eliminates all substitutions that could have a negative effect on phenotype, as shown in the case of low-altitude deer mice [87] and four different Gerbillus species [55]. The second reason behind genetic differentiation between populations may be specific morphological and reproductive differences in different climates.…”
Section: Discussionsupporting
confidence: 71%
“…Cytb gene sequence is characterized by both slowly and rapidly evolving codon positions as well as conserved and variable regions, which makes it ideal for deciphering diversity and systematics questions starting from detailed phylogeny [45][46][47][48][49][50] to the population and recent divergence levels [51][52][53][54]. Cytb gene variability can be used to identify the signs of adaptive evolution [55] as well as local declines in diversity, which is indicative of selective sweeps [56,57].…”
Section: Introductionmentioning
confidence: 99%
“…We aligned the sequences in BioEdit (Hall 1999) and removed the beginning and the end of all the sequences used in the analysis because these parts of the sequences were missing in all the seven individuals of G. amoenus from Egypt available in GenBank (Khalifa et al 2018), and we maintained a fragment of 942 bp. We constructed a phylogenetic tree using the maximum likelihood (ML) method in the software MEGA 7.0.26 (Tamura et al 2013) to estimate the evolutionary relationships among the sequences.…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid sequence of cytochrome b among human to parasite species has been delineated in a study of mitochondrial respiratory chain inhibitors with the zebrafish model for mitochondria-linked disorders [23]. Cytochrome b is the only protein product of the mitochondrial genome that is a fully functional monomer and is used for developing markers for genetic stock identification, as a primary population genetic indicator in many fish species and for phylogenetic and taxonomic purposes, making it a pragmatic gene to study for a project such as this due to the amount of data already in the literature [24,25]. Thus, differences in the amino acid sequence of cytochrome b subunit Qi of complex III are functionally relevant for delineating differences among fish species at the target site of ANT-A binding.…”
Section: Introductionmentioning
confidence: 99%